Memórias e imagens em confronto: os Xucuru-Kariri nos acervos de Luiz Torres e Lenoir Tibiriçá. - Peixoto, José Adelson Lopes (2013)
This paper proposes an analysis of the image of Indians Xucuru Kariri from Alagoas State (AL-Brazil) based on two photographic collections. The first, formed by Luiz de Barros Torres, still in the mid-twentieth century, is an extensive imagery documentation of Palmeira dos Indios city, and it is today under the responsibility of the Núcleo de Estudos Políticos, Estratégicos e Filosóficos (NEPEF) of State University of Alagoas (UNEAL). The second collection formed by the private collection of the former shaman of the village Mata da Cafurna, Lenoir Tibiriçá gathers registers of political and cultural movements of the latest resumption of lands. This work is based on a literature review ever produced about Xucuru Kariri, and tries to, through a fieldwork in the Mata Cafurna village, understand how these Indians perceive themselves in the images of these collections. The Indians images broadcasted in Palmeira dos Indios city also offer other perspectives that help questioning how Indians are perceived outside the village. The photographs are presented in the form of boards, and organized from the method developed by Gregory Bateson and Margaret Mead. Anyway, the images and memories in the two collections raise different views and reveal various ways of being Xucuru-Kariri indians in a dialogue with historical and anthropological research ever conducted in other works.